Molecular Interaction for the binary system of o-chloro phenol with methanol,ethanol, 1-propanol and 2-propanol at 298.15K by measuring the densities and viscosities (Journal of the College of Basic Education, 2022)
this project are studied the molecular interaction for the binary system thatis contained o-chlorophenol with methanol, ethanol, 1-propanol,and 2-propanolby measuring the densities ,and viscosities than conferred this to excess molarquantities by get the excess molar volume and deviation from viscosities andexplain this by two figure Than get the standared divation and parameters to theeqution of polynomial by using Redlick – Kister form.